(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Phytochemicals are secondary metabolites produced by all plants in which some have medicinal uses. The phytochemical analysis of peel & rhizome extracts in aqueous, ethanol, acetone, hexane, and chloroform extracts of indigenous medicinally important plants of citrussinensis (peels) &curcumalonga(dried rhizomes) were investigated. The phytochemical analysis revealed the presenceofactive constituents such as carbohydrates, flavonoids, alkaloids, terpenes, phytosterols, tannins, steroids, saponins, glycosides, phenols, and anthraquinones. This research supports the local use of the peel and rhizome extracts of orange and turmeric to show the potent nature of the sealants when using din combination to treat helminthiasis. These plants belong to family rutaceae & zingiberaceae respectively. The present study provides evidence that the solvent extract of citrussinensis and curcumin along contains medicinally important bioactive compounds and this just if is the use of these plants in combination to treat helminthiasis & control mode growth in intestines.